Sonography of Salivary Gland Tumors and Disorders - Johnson, Felix; Bozzato, Alessandro; Mansour, Naglaa; Mantsopoulos, Konstantinos; Psychogios, Georgios; Zengel, Pamela; Hofauer, Benedikt (Ultraschall in der Medizin - European Journal of Ultrasound, 2025)
Diseases of the salivary glands are as common as they are diverse and can have different causes. Clinicians can differentiate salivary gland changes based on chronic systemic diseases, congenital and vascular malformations, and benign and malignant tumors. Acute infectious pathologies can also arise as a result of obstructive pathologies. A large number of diseases with similar clinical presentations have to be differentiated. Due to the improved resolution of ultrasound technology over the last 20 years, it is now used as the first imaging modality to examine salivary gland pathologies. It allows a quick, dynamic, and non-invasive examination of the salivary glands and the soft tissue of the neck. In order to accurately diagnose and treat patients, a very good knowledge of these diseases and their appearance on sonography is required.Erkrankungen der Speicheldrüsen sind ebenso häufig wie vielfältig und können unterschiedliche Ursachen haben. Kliniker können Speicheldrüsen-Veränderungen in chronische systemische Krankheiten, angeborene und vaskuläre Fehlbildungen sowie gutartige und bösartige Tumoren differenzieren. Akute infektiöse Pathologien können auch als Folge obstruktiver Pathologien entstehen. Eine Vielzahl von Erkrankungen mit ähnlichem klinischem Erscheinungsbild müssen voneinander abgegrenzt werden. Aufgrund des verbesserten Auflösungsvermögens der Ultraschall-Technik in den letzten 20 Jahren wird diese nun als erste Bildmodalität zur Untersuchung von Speicheldrüsen-Pathologien verwendet. Sie erlaubt eine schnelle, dynamische, und nicht invasive Untersuchung der Speicheldrüsen sowie des Halsweichteils. Um Patienten genau diagnostizieren und behandeln zu können, ist eine sehr gute Kenntnis dieser Krankheiten sowie deren Erscheinungsbilder in der Sonografie erforderlich.
Keywords: Speicheldrüsen; Sialadenitis; Sialolithiasis; Pleomorphes Adenom; Warthin Tumor